Integrating Access Methods to Text Data Files - Shepherd, Michael A.; Watters, Carolyn (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
DalText is a prototype information retrieval system that permits the user to select access methods based on the task at hand. The system integrates multiple access techniques to textual data that are not maintained in traditional database management systems or information retrieval systems. The access methods available include viewing the data as a sequence of records for browsing.